2016
DOI: 10.3332/ecancer.2016.635
|View full text |Cite
|
Sign up to set email alerts
|

Successful palliative approach with high-intensity focused ultrasound in a patient with metastatic anaplastic pancreatic carcinoma: a case report

Abstract: We report a case of a 74-year-old man with a metastatic anaplastic pancreatic carcinoma (APC). After an early tumour progression on first-line chemotherapy with cisplatin and gemcitabine, even though it was badly tolerated, he was treated with a combination of systemic modified FOLFIRI and high-intensity focused ultrasound (HIFU) on the pancreatic mass. A tumour showing partial response with a clinical benefit was obtained. HIFU was preferred to radiotherapy because of its shorter course and minimal side effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Similar effects have been observed by others [114, 130132]. In all cases, patients received systemic chemotherapy concurrently with FUS treatments, but chemotherapy had been ineffective prior to initiation of FUS therapy.…”
Section: Introductionsupporting
confidence: 81%
“…Similar effects have been observed by others [114, 130132]. In all cases, patients received systemic chemotherapy concurrently with FUS treatments, but chemotherapy had been ineffective prior to initiation of FUS therapy.…”
Section: Introductionsupporting
confidence: 81%
“…The patient was treated with this drug achieving a complete response (CR) after 2 cycles and a disease-free survival of 23 months. 46 Ungaro et al 47 reported the lack of activity of cisplatin plus gemcitabine in a patient who received FOLFIRI in combination with high-intensity focused ultrasound with a PR. Shinagare et al 48 described the history of a patient treated with FOLFIRINOX who showed a PR even if OS was only of 5 months because of the deterioration of the clinical status.…”
Section: Undifferentiated (Anaplastic) Carcinomamentioning
confidence: 99%
“…This may result in mechanical damage to the tissue in the absence of a significant temperature change [24]. Focused ultrasound has been used to treat pancreatic cancer either as a standalone treatment or in combination with chemotherapy and/or radiotherapy [25][26][27][28]. For example, a clinical review of 3022 patients with advanced pancreatic cancer showed that treatment with HIFU ablation alone, or in combination with chemotherapy, resulted in a median survival of 10 months, whereas treatment with chemotherapy alone yielded a median survival of 7.6 months.…”
Section: Introductionmentioning
confidence: 99%